(untitled) (Altre Modernità, 2010)
In his famous work The Rhetoric of temporality, Paul de Man alluded to William Wordsworth as «one of the few poets who can write prolectically about his own death and speak, as it were, from beyond their own graves». My paper explores this kind of prolectic writing about death: cases in which authors write about themselves as if they were already dead. I analyze texts of three major poets of the second half of the 20th Century: Jaime Gil de Biedma, José Ángel Valente and Alfonso Costafreda -members of the so called Generación del 50 in Spanish Poetry. My aim is to think about the philosophical implications of these fictional attempts of writing about death confronted to Heidegger’s remark about the impossibility of experiencing one’s death. This article contributes to clarify how experience of death in Late Modern Poetry is related to a more lucid approach to finitude once all kind of eschatological or metaphysical projections have entered a deep crisis.